Goblin secrets - Alexander, William (William Joseph), 1976- (Margaret K. McElderry Books, 2012)
Hoping to find his lost brother, Rownie escapes the home of the witch Graba and joins a troupe of goblins who perform in Zombay, a city where humans are forbidden to wear masks and act in plays.